Model-based monocular 6-degree-of-freedom pose tracking for asteroid - Tang, Hao; Liu, Chang; Su, Yuzhu; Wang, Qiuyin; Hu, Weiduo (Frontiers in Space Technologies, 2024)
In this paper, we present a novel vision-based framework to track the 6-DoF pose of an asteroid in real time with the 3D contour of the asteroid as feature. During pose tracking, at the beginning time of tracking, the tracking system is initialized by a pose retrieval method. At each subsequent time instant, Given the 3D mesh model of an asteroid, with the initial pose and its covariance given by the square root cubature Kalman Filter (SCKF), the 3D mesh segments constituting the 3D asteroid contour are efficiently extracted from the 3D mesh model. Then, in the input asteroid image, we search the image points corresponding to the extracted 3D segments within the searching range defined by the initial pose and its covariance. After that, the asteroid pose is determined in real time by minimizing the angles between the back-projection lines of the searched image points and the projection planes of the corresponding 3D segments, which is much robust to the position change of the asteroid and asteroid size. The covariance matrix of the pose is inferred from the Cartesian noise model in the first order. Eventually, the SCKF is derived from the second-order autoregression to generate the final pose estimate, and give the initial pose and its covariance for next time instant. The synthetic trials quantitatively validate the real-time performance, robustness, and accuracy of our algorithm to dark space, different imaging distances, lighting condition, image noise, model error, and initial pose error, and meanwhile the real trial qualitatively shows the effectiveness of our method.